PENGGUNAAN MEDIA KARTU BERGAMBAR MELALUI MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR - Henny Setiani; Nanda Rahmadanis; Siti Nurjanah; Dyana Poncowati; Rahnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students’ learning outcomes in science subjects through the application of the Discovery Learning model assisted by animal picture card media. The research was conducted on third-grade elementary school students. The method used in this study is a classroom action research method with two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The results showed that the application of the Discovery Learning model with picture card media can improve student learning outcomes. This is evidenced by an increase in the average score and the percentage of student learning completeness from cycle I to cycle II. Therefore, this learning model is effective in improving students’ understanding of science material, especially animal topics.